PHYTOCHEMICAL SCREENING, FORMULATION AND EVALUATION OF FOOTSPRAY CONTAINING HONEY PINEAPPLE PEEL EXTRACT (ANANAS COMOSUS [L.] MERR) - Dwi Endah Kusumawati; Azmi Rahmadani; Rega Putri Puspitasari; Fahreza Maulana Ghazi; Ahmad Nida'ul Husna (Universitas Muhammadiyah Magelang, 2023)
Foot odor or bromhidrosis occurs due to the activity of bacteria that convert leucine in sweat into isovaleric acid which results in unpleasant odors. Honey pineapple skin (Ananas comosus [L.] Merr) is generally waste, whereas honey pineapple skin is known to contain antibacterial compounds. The aim of this study is to determine the potential of honey pineapple peel as an active ingredient in footspray based on the results of phytochemical screening and physical evaluation. Honey pineapple peel was extracted by maceration method using ethanol 70% then phytochemical test. Footspray preparations were made with various extract concentrations of 0%, 25%, 35% and 45% then tested for organoleptic, pH, specific gravity, viscosity, homogeneity, spreadability, and dry time during storage period of 0, 7, 14 and 21 days at room temperature. This study showed that honey pineapple peel extract contained flavonoids, tannins, phenols and alkaloids. The footspray has brown color with honey pineapple scent, pH of 5.71-6.37, specific gravity 1.05-1.09 g/mL, viscosity 7.2-13.2 cP, spreadability 6.67-7.60 cm, and the dry time is 4-5 minutes. Footspray containing honey pineapple peel extract with concentrations of 25%, 35% and 45% has a pH value that is safe for the skin, with good specific gravity, viscosity, homogeneity and spreadability, also stable during storage. Formula 1 (25% extract concentration) tends to be preferred because its texture is soft and not too sticky when applied to the skin when compared with formula 2 and 3.